2010
DOI: 10.1093/heapro/daq053
|View full text |Cite
|
Sign up to set email alerts
|

Engaging with nature to promote health: bridging research silos to examine the evidence

Abstract: While there is considerable research on environmental contamination and degradation, there is equally credible evidence on the healthful qualities of the environment. Being in and caring for nature can be health promoting for individuals, families, communities, ecosystems and the planet. In this paper, we use a conceptual model for nature-based health promotion and a socio-ecological model of health promotion to guide the scope, organization and critique of relevant literature on nature-based health promotion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Looking to the future, horticulture in prisons offers an important opportunity to connect policy agendas through enhancing learning and health literacy; building skills and enhancing employability; developing social and interpersonal skills and the competence to maintain family relationships; and promoting models of good citizenship (Baybutt and Chemlal, 2016). However, for this to have a meaningful and sustained impact on health inequalities and social exclusion within the UK and across the globe, policy – supported by further research – has a key role to play in overcoming the long-standing challenge of transitional and resettlement issues for prisoners and find ways to use programmes such as GOOP as catalysts for wider systemic and integrative change (Baybutt and Chemlal, 2016; Hansen-Ketchum and Halpenny, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking to the future, horticulture in prisons offers an important opportunity to connect policy agendas through enhancing learning and health literacy; building skills and enhancing employability; developing social and interpersonal skills and the competence to maintain family relationships; and promoting models of good citizenship (Baybutt and Chemlal, 2016). However, for this to have a meaningful and sustained impact on health inequalities and social exclusion within the UK and across the globe, policy – supported by further research – has a key role to play in overcoming the long-standing challenge of transitional and resettlement issues for prisoners and find ways to use programmes such as GOOP as catalysts for wider systemic and integrative change (Baybutt and Chemlal, 2016; Hansen-Ketchum and Halpenny, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Contact with the natural environment improves mental wellbeing – reducing stress and improving mood, providing a restorative environment and facilitating social contact (O’Brien et al , 2011; Sempik et al , 2005). Studies suggest that connecting with nature can restore cognitive attention (Kaplan, 1995), positively influence blood pressure and self-esteem (Pretty et al , 2007), decrease symptoms of deficit disorder (Kuo and Faber-Taylor, 2004), facilitate recovery from surgery (Ulrich, 1984) and increase perceived quality of life, strengthen community cohesion and motivate pro-environmental behaviour (Hansen-Ketchum and Halpenny, 2011). Buck [Buck (2016), p. 6] reports that evidence of the benefits of gardening for health is complex but that ‘observational and qualitative studies are consistent with a wide range of health impacts across mental and physical health and health behaviours across the life-course.’ O’Brien et al [O’Brien et al (2011)] suggest that active hands-on engagement with nature is effective in enabling marginalized people to reintegrate into society by facilitating skills development, improving self-confidence, creating social networks, providing meaningful activity and developing a sense of responsibility.…”
Section: Introductionmentioning
confidence: 99%
“…The results of our study showed that using N-BS can reduce pain. In this regard, a study by Hansen-Ketchum and Halpenny (17) reported that the N-BS intervention provides conditions that foster human and environmental health by reducing anxiety and enabling psychological and physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recognition of the potential for these links has led to increasing awareness of potential for the outdoor environment, whether built or natural, to be used as a setting for health-promoting activity [ 6 , 7 ]. One approach to achieving health-gain though the use of outdoor environments are environmental enhancement and conservation activities, which could be of benefit through the process of active participation but also through improved environments.…”
Section: Introductionmentioning
confidence: 99%